Yanama, eco hábitat Wayuu en la Alta Guajira (2021)
This project focuses on the approach of bioarchitecture in a desert context of northern Colombian La Guajira, specifically in the municipality of Manaure, where the Wayuu community has its most important settlement allowing to identify a series of problems related to the economy, public services, housing and its quality and nutritional health in these communities. Taking into account the above, an eco-habitat is proposed that covers social, productive, housing and tourism issues, implementing local materials that are easy to obtain and non-polluting, allowing the manufacture of this project with quality and sustainable design as the main pattern that respects and is inclusive with the cosmological beliefs of this culture.